The effect of ion environment changes on retention protein behavior during whey ultrafiltration process - Wen-qiong Wang; Jian-ju Li; Ji-yang Zhou; Man-xi Song; Jia-cheng Wang; Xing Li; Cong-Cong Tang; Mao-lin Lu; Rui-xia Gu (Food Chemistry: X, 2022)
The factors affecting membrane fouling are very complex. In this study, the membrane fouling process was revealed from the perspective of ion environment changes, which affected the whey protein structure during ultrafiltration. It was found that the concentrations of Ca2+ and Na+ were overall increased and the concentrations of K+, Mg2+ and Zn2+ were decreased at an ultrafiltration time of 11 min, which made more hydrophilic groups buried inside and increased the content of α-helix, leading to more protein aggregation. The relatively higher K+ ratio in retention could lead to an antiparallel β-sheet configuration, aspartic acid, glutamic acid and tryptophan increased, which resulted in more protein aggregation and deposition on the membrane surface at 17 min. When the ion concentration and ratio restored the balance and were close to the initial state in retention, the protein surface tension decreased, and the hydrophilic ability increased at 21–24 min.